2024
DOI: 10.3390/f15030427
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Seedling Growth and Physiological Performances of Melia azedarach L. by Foliar Application of 24-Epibrassinolide under Salt Stress

Zin Myo Htet,
Xiaoxian Li,
Fangyuan Yu

Abstract: Salinity is a serious environmental problem following a worsening trend. This study investigates the role of 24-epibrassinolide(EBR) in regulating plant growth and physiological performances, particularly in alleviating the negative effects of salt stress. Melia azedarach L. seedlings from two seed sources, Sheyang (SY) and Xiashu (XS), were exposed to sea salt and treated with different concentrations of EBR within a 60-day period. The results demonstrate that appropriate EBR application improved the seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(148 reference statements)
0
0
0
Order By: Relevance
“…Htet et al [6] explored the role of 24-epibrassinolide (EBR) in regulating the growth and physiological performance of Melia azedarach seedlings from two different seed sources under varying salt stress levels over a 60-day experimental period. Their main finding indicated that the appropriate application of EBR enhanced seedling stress tolerance by promoting growth and physiological systems.…”
Section: Adaptation To Salt Stressmentioning
confidence: 99%
“…Htet et al [6] explored the role of 24-epibrassinolide (EBR) in regulating the growth and physiological performance of Melia azedarach seedlings from two different seed sources under varying salt stress levels over a 60-day experimental period. Their main finding indicated that the appropriate application of EBR enhanced seedling stress tolerance by promoting growth and physiological systems.…”
Section: Adaptation To Salt Stressmentioning
confidence: 99%